Types of questions asked by elementary school children about mathematics - Ferrancullo, Felixberto A. (1978)
The focus of this study was to find out the type of question most often asked by school children about mathematics. The subjects of the study were grades 4-6 pupils in five public schools in Manila. A 30-minute interaction for each class was tape-recorded. The topics involved in the pupils' questions were classified and analyzed. The study concluded that the questions asked by the subjects were oriented towards understanding the basic concepts and procedures in elementary mathematics. The specific topics that the subjects found difficult to understand were finding the LCF and the process of dividing whole numbers.